A hydrodynamical perspective on the turbulent transport of bacteria in rivers - Werner, Michael (Dissertationsreihe am Institut für Hydromechanik, Karlsruher Institut für Technologie, 2023)
The transport of bacteria in turbulent river-like environments is addressed, where bacterial populations are frequently encountered attached to solids. This transport mode is investigated by studying the transient settling of heavy particles in turbulent channel flows featuring sediment beds. A numerical method is used to fully resolve turbulence and finite-size particles, which enables the assessment of the complex interplay between flow structures, suspended solids and river sediment.